2023
DOI: 10.1093/bjsopen/zrad040
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical bowel preparation and antibiotics in elective colorectal surgery: network meta-analysis

Abstract: Background The use of intravenous antibiotics at anaesthetic induction in colorectal surgery is the standard of care. However, the role of mechanical bowel preparation, enemas, and oral antibiotics in surgical site infection, anastomotic leak, and other perioperative outcomes remains controversial. The aim of this study was to determine the optimal preoperative bowel preparation strategy in elective colorectal surgery. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…Multiple studies indicate that the incidence of postoperative complications, such as ALs and SSIs, remains unchanged when using preoperative antibiotic bowel preparation, regardless of whether it is administered with or without MBP. These findings prompt a reassessment of the standard preoperative regimen and suggest that preoperative oAB alone should be considered as the new standard of care [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies indicate that the incidence of postoperative complications, such as ALs and SSIs, remains unchanged when using preoperative antibiotic bowel preparation, regardless of whether it is administered with or without MBP. These findings prompt a reassessment of the standard preoperative regimen and suggest that preoperative oAB alone should be considered as the new standard of care [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies from the American College of Surgeons National Surgical Quality Improvement Program reignited the debate almost a decade ago and suggested that mechanical and oral antibiotic bowel preparation (MOABP) is associated with lower rates of SSIs in colorectal surgery compared with only mechanical bowel preparation (MBP) or no bowel preparation . A recent meta-analysis of randomized clinical trials (RCTs) found an approximately 50% reduction in SSIs when oral antibiotics are added to bowel preparation regimens . However, a crucial limitation of the RCTs included in the meta-analysis is that outcomes were not reported separately for rectal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] A recent meta-analysis of randomized clinical trials (RCTs) found an approximately 50% reduction in SSIs when oral antibiotics are added to bowel preparation regimens. 13 However, a crucial limitation of the RCTs included in the meta-analysis is that outcomes were not reported separately for rectal surgery. Rectal surgery is often preceded with neoadjuvant radiotherapy or chemoradiotherapy and, due to higher rates of anastomotic dehiscence especially in low anastomoses, a protective stoma is often used.…”
mentioning
confidence: 99%
“…Another area of coloproctology that divides opinion is the use of mechanical bowel preparation and preoperative oral and intravenous antibiotics. A network meta-analysis comprising 60 RCTs and 16 314 patients 4 aimed to determine the optimal bowel preparation strategy. The authors concluded that oral and intravenous antibiotics with or without mechanical bowel preparation reduced surgical site infection and anastomotic leaks and should be the standard of care.…”
mentioning
confidence: 99%